Characterisation, modelling and tribological investigations of nano-structured TiC-based electrical discharge coatings - Algodi, Samer Jasim Mahmood (2018)
Electrical discharge coating (EDC) is a surface modification process used to produce hard coatings from a sacrificial powder metallurgy (PM) tool electrode onto a target workpiece. However, the integrity of as-processed EDC surfaces, as reported on in literature, is generally poor, with limited understanding of the fundamental interactions between energy source and workpiece material, and the microstructural development of the surfaces created. This thesis explores, at the nano-scale, the deposition and microstructural development of ED processed cermet coatings. Emphasis is given to TiC-based ED coatings, prepared using a semi-sintered TiC tool electrode. A comprehensive study of TiC/Fe cermet coating microstructural development, as a function of ED processing conditions (current 2 - 19 A; pulse-on time 2 - 64 µs) is presented, using the combined characterisation techniques of scanning electron microscopy (SEM) / energy dispersive X-ray spectroscopy (EDS), X-ray diffractometry (XRD) and cross-sectional transmission electron microscopy (TEM). The ED coatings were composites in nature, with complex banded nanostructures of TiC grains within an Fe matrix. Preferred TiC/Fe ED coatings on 304-SS, achieved under conditions of low processing energy (10 A current and 8 µs pulse-on time), exhibited low levels of cracks and porosity, with hardness values of ~ 1800 HV. The fraction of energy transferred to the workpiece, Fv, as a consequence of ED sparking, is an important parameter which affects directly individual crater geometry and the microstructural development of the near surface modified layer. Hence, a 2D transient heat transfer model is presented, using finite difference methods, and used to estimate effective values for Fv as a function of processing conditions, and thereby to predict coating layer thicknesses of developed microstructures through appropriate consideration of heat flow into the system. The model is validated against previous work in literature and with experimental observations. The modelling demonstrated a variation of energy transferred to the workpiece, of 17 - 23% for increasing current from 2 - 19 A at fixed pulse-on time of 8 µs; and 7 - 53% for increasing pulse-on time from 2 - 64 µs at fixed current of 10 A. Predictions for heat transfer and the cooling of melt pools, arising from single spark events, compared well with experimental observations for the development of these TiC/Fe cermet microstructures. The cooling phase had two distinct stages, with initial rapid non-uniform cooling within the first ~ 10 - 20 µs leading up to the onset of TiC crystallisation, followed by a more uniform stage of heat loss up to ~ 100 µs, leading up to the onset of Fe matrix solidification. The tribological behaviours of TiC/Fe ED cermet coatings on both HSS and 304-SS substrates were investigated, with reference Cu EDM surfaces. The wear resistance of these cermet coatings, on both substrate types, yielded dry sliding wear resistances up to two orders of magnitude greater than that of the substrate. Further, EDC cermet coatings on HSS were typically 2 - 4 times more wear resistant, depending on loading, than those deposited on 304-SS, with wear performances reflecting the composite nature of the coatings coupled with the mechanical properties of the substrates. Laser surface treatments, used to improve the surface integrity of the as-deposited coatings, through the elimination of cracks and porosity, acted to increase the wear rate for all samples, with the exception of coatings on HSS under conditions of high loading. The general increase in wear rate was attributed to a significant reduction in the proportion of TiC within the ED coatings, after laser treatment, combined with an increase in grain size; whilst improvements to the wear performance of laser treated, cermet coated HSS, under high loading, was attributed to the avoidance of an abrasive wear mechanism.